Answer: 4 a - 3 b
Step-by-step explanation:
Since, the perimeter of the triangle = sum of all the three side of the triangle.
Here, two sides of the triangle are 2a + b and a - 9b,
And, the perimeter of the triangle = 7 a - 11
Let third side = x
Therefore, 2 a + b + a - 9 b + x = 7 a - 11 b
⇒ 3 a - 8 b + x = 7 a - 11 b
⇒ x = 7 a - 11 b - 3 a + 8 b
⇒ x = 4 a - 3 b ( by operating like terms)
4; enlargement !! hope this helps
I think $16,250 tax. If you need explanation comment
Answer:
44805
Step-by-step explanation:
Answer:
Assuming that a and b are not the hypotenuse then B would be equal to A, so B would equal 25m
Step-by-step explanation:
I hope this is right, you didn't put a picture.